Neuroanatomy in Rett Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1997)
Volumetric MRI analyses of the cerebral cortex and posterior fossa of 20 girls with Rett syndrome (RS) were compared with individually-matched normal controls at the Kennedy Krieger Institute, The Johns Hopkins University School of Medicine, Baltimore, MD.